Drying of butiá pulp by the foam-layer method and characterization of the obtained powder - Girelli, Andreza; Sant’Anna, Voltaire; Klein, Manuela Poletto (Pesquisa Agropecuaria Brasileira, 2024)
The objective of this work was to develop a drying process using the foam-layer method to obtain the powder from butiá (Butia spp.) pulp, as well as to characterize this powder according to its yield and physicochemical and technological characteristics. The foam was optimized for density and stability by varying whipping times and albumin and xanthan gum concentrations. Foam drying was optimized for vitamin C retention and yield using different foam thicknesses and drying temperatures. The optimized foam showed a density of 0.25 g cm-3 and a high stability, being suitable for subsequent drying. The lowest foam thickness (0.50 cm) and the highest drying temperature (80°C) resulted in the highest retention of vitamin C, whereas the increase in drying temperature improved yield. The butiá pulp powder obtained under the optimized condition presented an acid pH of 3.25, a low humidity of 7.97%, a water activity of 0.206, a water retention capacity of 4.90 g H2O per gram of powder, a solubility of 74.40%, a soluble solids content of 61°Brix, and a predominantly yellow color. The foam-layer drying method can be used to obtain butiá pulp powder.